Feed mills for on-farm feed manufacturing - James P Murphy; Joseph P Harner (Kansas Agricultural Experiment Station Research Reports, 1990)
Quality feed can be manufactured on farm using hammer or roller mills for particle size reduction and volumetric or weighing devices for proportioning ingredients. An understanding of each of the seven steps involved will enhance the ability to manufacture a quality feed for maximum feed efficiency at a feasible price.; Swine Day, Manhattan, KS, November 15, 1990
Keywords: Swine day; 1990; Kansas Agricultural Experiment Station contribution; no. 91-189-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 610; Swine; Process; Diets